Analysis of Material Processes in Donald Trump’s Inauguration Speech Text and Their Translation - Faris Hamzah (Pioneer: Journal of Language and Literature, 2017)
This qualitative research is about material process and technique of translation in Donald Trump’s inauguration speech text. The data source is Donald Trump’s inauguration speech text and the research data are in the form of clauses that contain material processes in inauguration speech of Donald Trump. The researcher used the theory proposed by Spradley (1998) in analyzing the data. The research was conducted by accomodating two theories: the theory of material process proposed by Halliday (2004) and the theory of translation techniques proposed by Molina and Albir (2002). The result of this study shows that there were 119 data found in inauguration speech of Donald Trump that are relevant with the research problem. and the researcher found eleven generalization, particularization, linguistic compression, linguistic amplification, modulation, compensation, reduction, literal translation, and transposition. The use of literal translation technique is dominant than other techniques in this research. The researcher found 94 data that contains literal translation technique in the research findings where type of doing 67 and happening 27. Besides, the less of translation techniques used are borrowing, reduction, and linguistic amplification with one data. Literal technique is the most frequent because this technique does not distort meanings in the source language; thus, the meanings can be conveyed into the readers in target language well. The researcher expects the next researchers to do analysis on translation with other object of research.